2-Aminoethoxydiphenyl borate activates the human mechano-gated KCNK channels KCNK 2 (TREK-1), KCNK 4 (TRAAK) and KCNK 10 (TREK-2). - Leopoldo Raul Beltran; Madeline eBeltran; Ainhara eAguado; Guenter eGisselmann; Hanns eHatt (Frontiers Media S.A., 2013)
Abstract: Two-pore domain K+ (KCNK, K2P) channels underlie the leak (background) potassium conductance in many types of excitable cells. They oppose membrane depolarization and cell excitability. These channels have been reported to be modulated by several physical and chemical stimuli. The compound 2-aminoethoxydiphenyl borate (2-APB) was originally described as an inhibitor of IP3-induced Ca2+ release but has been shown to act as either a blocker or an activator for several ion channels. Here, we report the effects of this compound on members of the TREK subfamily of human KCNK channels. We injected Xenopus laevis oocytes with cRNAs encoding several KCNK channels and measured their response using the two-electrode voltage clamp technique. 2-APB was found to be an effective activator for all members of the TREK subfamily (hKCNK2, hKCNK4 and hKCNK10), with the highest efficacy in hKCNK10. We also found that 2-APB was able to activate these channels in cell-excised patches of HEK293 cell transfected with hKCNK4 or hKCNK10, demonstrating direct activation. TREK channels are widely expressed in the CNS and peripheral tissues, where they play roles in several key processes. However, little is known regarding their pharmacology; therefore, the identification of a common, stable and inexpensive agonist should aid further investigations of these channels. Additionally, 2-APB has been used to study native receptors in cell systems that endogenously express members of the TREK subfamily (e.g. rat dorsal root ganglia); our results thus warn against the use of 2-APB at high concentrations in these systems.